The Influence of Leadership and Organizational Commitment on Teacher Performance with Motivation as an Intervening Variable - Norawati, Suarni; Yanti, Kasmira; Basem, Zamhir; Yusup, Yusup (STKIP PGRI SITUBONDO, 2024)
Teacher performance is teaching achievement resulting from activities carried out by teachers in their main duties and functions in concrete realization which is a logical consequence as a professional in the field of education, therefore many factors influence teacher performance. The aim of this research is to determine and analyze the influence of 1) leadership on teacher work motivation; 2) commitment to teacher work motivation; 3) work motivation on teacher performance; 4) the direct influence of leadership on teacher performance; 5) the direct influence of organizational commitment on teacher performance; 6) the indirect influence of leadership on teacher performance through work motivation; 7) the indirect influence of organizational commitment on teacher performance through work motivation. The types of data in this research are primary data and secondary data. Data collection was carried out using questionnaires, observations, interviews and research files. The sample for this research was 26 teachers at SDN 5 Bathin Solapan. Analysis tools and hypothesis testing in this research were carried out using the Structural Equation Modeling (SEM) model, data processing was carried out using the SmartPLS program, and hypothesis testing was carried out at 5% alpha. The results of this research concluded that 1) leadership was proven to have a significant effect on teacher work motivation; 2) commitment is proven to have a significant effect on teacher work motivation; 3) work motivation has been proven to have a significant effect on teacher performance; 4) there is no direct influence of leadership variables on teacher performance; 5) there is no direct influence of the organizational commitment variable on teacher performance; 6) there is a significant indirect effect of leadership on teacher performance through work motivation; 7) there is a significant indirect effect of organizational commitment on teacher performance through work motivation.